Kajian pemikiran dan amalan refleksi di kalangan guru pelatih sains Universiti Teknologi Malaysia - Ibrahim, Nor Hasniza (2006)
The aim of this study was to investigate the effectiveness the implementation Model of Thinking Implementation Strategy and Reflective Practices in Science Teaching and Learning Process among the science student teachers during their practicum session. In an attempt to answer the above objective, the patterns and levels of reflective thinking of a group of students as in current practices were compared to a group of students that were exposed to the above model. The group of thirty undergraduate science student teachers of Universiti Teknologi Malaysia in several schools in Pontian and Johor Bahru were purposively chosen as the respondents of this study. The instruments used were science student teachers’ self-reflection in their daily lesson plans, respondents’ reflective journals and interviews. The patterns of students’ reflective writing were analyzed using Standard for Science Teacher Preparation that suggested by National Science Teacher Association (2003). While the levels of reflection were analyzed using categorization suggested by Hatton and Smith (1995). Interviews were transcribed and analysed using the technique of content analysis. The results show that the patterns of reflective writing of the science student teachers in the current practices are very superficially written and focus on the aspects of teaching and learning and do not contribute much in improving their teaching competencies. Besides that, the level of their reflective writings is only at the descriptive level. However, the patterns of reflective writings for the group that was exposed to the Model of Thinking Strategy and Reflective Practices have been improved very much. The science student teachers are able to reflect at dialogue and critical levels and have focus on the important aspects of science teaching and learning. The results have proved that the above model is effective to enhance the reflective thinking pattern and be able to improve reflective practices among the science student teachers. It is hope to increase the effectiveness of science teaching and learning process and to shed some lights on the formulation of an authentic curriculum in teacher education.